Evaluating the Impact of Marital Status on Employees’ Job Performance: Moderating Role of Hired Hand’s Gender - Waqar Aslam , Muhammad Hafeez , AhamdKhawarShahzad , Ashfaq Ahmad ,Maeenuddin,Maaz Ud Din , Mehran Khan (International Journal of Advanced Science and Technology, 2020)
The last few years observers discerned that employee performance of almost all types of organizations especially the academic side of education sectors plummeting day by day. Behind the dearth of this performance,researchers found number of factors that affect employee performance. Among these factors, one of the main causes of marital status playsa preponderant role in employee performance. So, the purpose of this study is to investigate the impact of marital status on employees’ job performance of universities’ academic faculty of district Shaheed Benazirabad. Under this investigation, we focused on four variables, marital status as an independent variable, job performance as a dependent variable, and gender as a moderating variable. Data was collected by Stratified Random Sampling Technique from three universities including Shaheed Benazir Bhutto University, Shaheed Benazirabad, Quaid-e-Awam University of Engineering, Science, and Technology, Shaheed Benazirabad and People University of Medical and Health Sciences for Women, Shaheed Benazirabad. Sample collected from two hundred respondents and analyzed through Statistical Package for the Social Sciences (SPSS) software. Due to the abnormality of data, we apply the “Mann-Whitney” non-parametric test for the predictor and outcome variables and“Regression” test for moderating variable. Therefore,on the basis of analyses, it was concluded that there is a positive significant relationship between marital status and job performance. However, information about this investigation isadvantageous for Human Resource Managers to prefer employees towards job activity and job satisfaction after being married.